Motivation and gender effect in receptive vocabulary learning: An exploratory analysis in CLIL primary education - Almudena Fernández-Fontecha (Universidad de La Sabana, 2014)
The present paper seeks to address the connection between the receptive vocabulary size and motivation towards EFL of a group of CLIL primary graders by paying special attention to learners' gender variation. In particular, our goal is to probe into (1) gender variation in EFL receptive vocabulary size, (2) gender variation in motivation towards the foreign language, and (3) the relationship between motivation towards the foreign language and scores in a receptive vocabulary test. No statistically significant differences are found on gender variation neither in EFL receptive vocabulary size nor in motivation, both boys and girls follow quite similar patterns; finally, we have identified a positive correlation between boys' levels of intrinsic motivation and the number of words they know receptively. The waning effect of CLIL on gender variation, as shown in previous research, is adduced here as one of the possible sources of lack of differences both in vocabulary achievement and motivation.